THE INFLUENCE OF WORK COMPETENCE, WORK CULTURE, AND WORK DISCIPLINE ON JOB SATISFACTION IN EMPLOYEES THE ROS IN HOTEL YOGYAKARTA - Farikhah, Tiya Rindang; Prayekti, Prayekti (International Conference on Humanity Education and Society (ICHES), 2024)
Job satisfaction reflects a person's feelings that appear in the employee's positive attitude towards work and everything that is faced in the company's environment. This study aims to examine and analyze the effect of work competence, work culture, and work discipline on employee job satisfaction. This research was conducted on employees of Ros in Hotel Yogyakarta using quantitative methods and collection using questionnaires with a sample of 60 employees. Sampling using sampling saturated sampling techniques, while for data processing using multiple linear regression analysis. The results showed that job competence does not have a positive effect on job satisfaction. However, work culture and work discipline have a positive effect on job satisfaction.